The past is prologue part II: a study of PDS comparison dissertations - Diane Yendol-Hoppey; Eva Garin (Emerald Publishing, 2023)
Purpose - The study aims to present a logic map linking the Professional Development School (PDS) Nine Essentials as a PDS theory of action and offer an analysis of dissertations that compare outcomes of learning in PDS and non-PDS contexts. Design/methodology/approach - For this current study, the authors identified 25 of the 210 dissertations from a larger study that used a comparison methodology to provide a window into how learning in PDS and non-PDS settings may differ. In reviewing these comparison studies, the authors identified a set of clustered themes, as well as a variety of comparison constructs and measurements researchers used to determine the impact of PDS. Findings - Five themes emerged including (1) the experience of learning to teach in a PDS setting vs. a non-PDS; (2) the experience of teaching in a PDS vs. non-PDS; (3) teacher candidate quality in a PDS vs. non-PDS; (4) teacher quality in a PDS vs. non-PDS; (5) school leader quality in a PDS vs. non-PDS; and (6) K-12 student learning in PDS vs. non-PDS. Research limitations/implications - Limitations of this study include the complications related to comparison, logic-related fallacies and the complexity of capturing simultaneous renewal. Originality/value - In the 30th year of PDS work, the study utilizes a theory of action comprised of linking the PDS Nine Essentials to situate the comparison dissertation analysis of outcomes in PDS and non-PDS contexts suggesting challenges and possibilities and perhaps a direction for new research questions.